Criticising the Implementation of the ACTIP in Southeast Asia - Belardo Prasetya Mega Jaya; Ridwan Ridwan; Rully Syahrul Mucharom; Dwi Edi Wibowo; Siti Nur Aisah; Sulastri Sulastri; Novia Bella Alifvia (Sriwijaya Law Review, 2023)
The legal framework for ASEAN cooperation in combating the crime of trafficking in persons, particularly women and children, led to the establishment of the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP). This convention recognises that trafficking constitutes a violation of human rights and a crime against human dignity. However, the implementation of ACTIP faces numerous challenges that require strategic solutions. This research aims to examine the implementation of the ACTIP policy concerning human trafficking, assess ASEAN's efforts in tackling trafficking in women and children in the Southeast Asian region, and criticise the implementation of ACTIP. The research adopts a descriptive-normative method. The ACTIP Convention regulates provisions for dealing with trafficking problems, both prevention and handling, which are the responsibility of the central and local governments as well as the community by establishing various task forces in the implementation of prevention and control of human trafficking that occurs. ASEAN has taken several steps in the fight against human trafficking. Many obstacles must be faced to eradicate the criminal act of trafficking in persons. So. it is necessary to take several actions in implementing the ACTIP. ASEAN Members must cooperate either bilaterally or multilaterally so that the ACTIP arrangement can be implemented effectively.